THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL TO INCREASE STUDENTS’ MATHEMATICAL PROBLEM SOLVING FOR GRADE VIII AT SMP NEGERI 37 MEDAN 2019/2020 - Rosinta Meissi Sitinjak; Erlinawaty Simanjuntak (Universitas Negeri Medan, 2019)
Abstract: This study aimed to increase students’ mathematical problem solving ability in the numerical pattern material by using problem based learning model in grade VIII of SMP Negeri 37 Medan.. This research was a classroom action research conducted in 2 cycles, each cycle consisted of two meetings, where at the end of each cycle a test of students mathematics problem solving ability (TKPM) was given. The results showed that: in the cycle I, the level of TKPM was moderate with an average value of 68.22, the students who achieved the target of success were 21 students from 32 students (65.625%), in the cycle II the level of TKPM was high with an average value of 80.82, the students who achieved success targets were 28 students from 32 students (87.5%). Based on the those results, it was concluded that the problem-based learning model increased students’ mathematics problem solving ability in class VIII of SMP Negeri 37 Medan in the academic year 2019/2020. Keywords: Problem Based Learning Model, Mathematics Problem Solving Ability Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan pemecahan masalah matematika siswa dengan menerapkan model pembelajaran berbasis masalah di kelas VIII SMP Negeri 37 Medan. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam 2 siklus, masing-masing terdiri dari dua pertemuan, dimana di akhir setiap siklus diberikan Tes Kemampuan Pemecahan Masalah (TKPM). Hasil penelitian menunjukkan bahwa: Pada siklus I, hasil TKPM siswa adalah sedang dengan nilai rata-rata 68,22, dimana siswa yang mencapai target keberhasilan adalah 21 orang dari 32 orang siswa (65,625%), pada siklus II TKPM siswa adalah tinggi dengan nilai rata-rata 80,82, dimana siswa yang mencapai target keberhasilan adalah 28 orang dari 32 orang siswa (87,5%), Berdasarkan uraian diatas disimpulkan bahwa model pembelajaran berbasis masalah dapat meningkatkan kemampuan pemecahan masalah matematika siswa di kelas VIII SMP Negeri 37 Medan T.A. 2019/2020. Kata Kunci: Model Pembelajaran Berbasis Masalah, Kemampuan Pemecahan Masalah Matematika